Dinamika Menjelang Pendirian Partai Rakyat Demokratik di Masa Orde Baru - Angga, Vicky Verry; Anggraini, Juwita (Institut Agama Islam Negeri Ponorogo, 2020)
ABSTRACTThe Orba government in carrying out its power is almost always repertive acts of the people. The Orba government also practiced an all-out democracy in the political practice of the day. The condition is inflicting discontent of young men and activists. In the 1992, the action committee began to appear and continue to evolve in the next years. The alliances of student alliances then flourished the role of the action committee. Student alliances evolved into a sectoral student organization, laborers, farms, and culture. Sectoral organizations make a struggle against Orba into boxes. The gathering of sectoral organizations then formed the Democratic People's Unity together in 1994, the Democratic People's Unity on its journey didn't go well, there was a difference of opinion between members. The Democratic People's Unity experiences split and delivers the idea of the party's establishment of members. The party's establishment through an uneasy process in the organization. The Extraordinary Congressman 1996 decided the Democratic People Party's foundation. Party is expected to make the movement get radical. Party as a symbol of resistance to your formal democracy system applied by Orba. The party can also be used as a media resistance against the Orba Hegemoni.ABSTRAKPemerintah Orba dalam melaksanakan kekuasaanya hampir selalu melakukan tindakan represif terhadap rakyat. Pemerintah Orba juga mempraktikkan demokrasi semu dalam praktik politik masa itu. Kondisi ini menimbulkan ketidakpuasan dari pemuda dan aktivis. Pada 1992, komite aksi mulai muncul dan terus berkembang di tahun-tahun berikutnya. Aliansi-aliansi mahasiswa kemudian berkembang mengantikan peran komite aksi. Aliansi mahasiswa berkembang menjadi organisasi sektoral mahasiswa, buruh, tani, dan kebudayaan. Organisasi sektoral membuat perjuangan melawan Orba menjadi terkotak-kotak. Kumpulan dari berbagai organiasi sektoral kemudian membentuk Persatuan Rakyat Demokratik sebagai wadah bersama pada 1994. Persatuan Rakyat Demokratik dalam perjalanannya tidak berjalan lancar, terjadi perbedaan pendapat antar anggota. Persatuan Rakyat Demokratik mengalami perpecahan dan melahirkan ide pendirian partai dari sebagian anggota. Pendirian partai melalui proses yang tidak mudah di dalam organisasi. Kongres Luar Biasa 1996 memutuskan pendirian Partai Rakyat Demokratik. Berdirinya partai diharapkan membuat pergerakan menjadi semakin radikal. Partai sebagai simbol perlawanan terhadap sistem demokrasi semu yang diterapkan Orba. Partai juga dapat digunakan sebagai media perlawanan terhadap hegemoni Orba.